2014
DOI: 10.1210/en.2014-1218
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Analog Liraglutide Enhances Proinsulin Processing in Pancreatic β-Cells via a PKA-Dependent Pathway

Abstract: Hyperproinsulinemia has gained increasing attention in the development of type 2 diabetes. Clinical studies have demonstrated that glucagon-like peptide-1 (GLP-1)-based therapies significantly decrease plasma proinsulin/insulin ratio in patients with type 2 diabetes. However, the underlying mechanism remains unclear. Prohormone convertase (PC)-1/3 and PC2 are primarily responsible for processing proinsulin to insulin in pancreatic β-cells. We have recently reported that Pax6 mutation down-regulated PC1/3 and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Previous reports already showed contradictory results in terms of GLP-1R expression within the liver 4, 5 , and we are not totally convinced that the band detected by the antibody in human samples really corresponds to GLP-1R (as it is contradictory to the two specific mRNA TaqMan probes). In agreement, additional experiments showed lack of protein kinase A phosphorylation (marker of GLP-1R activation) 31, 32 in response to liraglutide, and no differences in liraglutide-mediated HSC de-activation and proliferation when an antagonist of GLP-1R was used. Secondly, we analyzed the expression of the transcription factor Kruppel-like factor 2 (KLF2) in response to liraglutide since the effects of liraglutide on HSC were quite similar to those previously observed using statins 26, 3335 .…”
Section: Discussionsupporting
confidence: 72%
“…Previous reports already showed contradictory results in terms of GLP-1R expression within the liver 4, 5 , and we are not totally convinced that the band detected by the antibody in human samples really corresponds to GLP-1R (as it is contradictory to the two specific mRNA TaqMan probes). In agreement, additional experiments showed lack of protein kinase A phosphorylation (marker of GLP-1R activation) 31, 32 in response to liraglutide, and no differences in liraglutide-mediated HSC de-activation and proliferation when an antagonist of GLP-1R was used. Secondly, we analyzed the expression of the transcription factor Kruppel-like factor 2 (KLF2) in response to liraglutide since the effects of liraglutide on HSC were quite similar to those previously observed using statins 26, 3335 .…”
Section: Discussionsupporting
confidence: 72%
“…The present results support this hypothesis, as we showed that the effect of liraglutide on reversing AGEs-induced ROS production, pro-inflammatory cytokine secretion, and cell viability were mediated by the activation of cAMP/PKA signaling. Liraglutide was previously shown to upregulate the prohormone converting enzymes PC1/3, which process proinsulin to insulin in pancreatic β-cells, in vitro and in vivo through the activation of the GLP-1R/cAMP/PKA pathway [48]. In a mouse model of diabetic nephropathy, liraglutide showed a protective role against renal oxidative stress triggered by hyperglycemia mediated by cAMP/PKA activation [49].…”
Section: Bao Et Al: Relation Of Liraglutide and Glp-1r In Neuroprotementioning
confidence: 99%
“…Nevertheless, the underlying mechanism was still unclear. Otherwise, some data confirmed that GLP-1 possess a potent anti-inflammatory property through a PKA-dependent signaling pathway [ 19 , 20 , 21 , 22 , 23 , 24 ]. Arakawa et al [ 24 ] showed that LPS-induced macrophage activation and TNF-α expression was significantly reduced by GLP-1 analog exendin-4 through PKA/NF-κB signaling pathway.…”
Section: Introductionmentioning
confidence: 99%